2012
DOI: 10.1093/jpids/pis095
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Vasculopathy in HIV-Infected Children Enrolled in the Pediatric AIDS Clinical Trials Group 219/219C Study

Abstract: CNS vasculopathy in HIV+ children is uncommon but more common than in the general pediatric population. Cerebral aneurysms are the most common manifestation. Although the pathogenesis remains unclear, older children and those with low CD4 counts and high HIV viral loads are at the highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“… 2 , 3 The incidence of cerebrovascular events in pediatric patients with HIV infection is estimated to be 3.4 cases per 10000 person-years. 4 Human immunodeficiency virus–associated arteriopathy encompasses several forms of arterial diseases occurring in the absence of any cause other than HIV infection. The HIV–associated aneurysmal arteriopathy is a rare cerebrovascular complication of acquired immune deficiency syndrome (AIDS) and has been the subject of several case reports and case series involving children, and more recently adults, with AIDS.…”
mentioning
confidence: 99%
“… 2 , 3 The incidence of cerebrovascular events in pediatric patients with HIV infection is estimated to be 3.4 cases per 10000 person-years. 4 Human immunodeficiency virus–associated arteriopathy encompasses several forms of arterial diseases occurring in the absence of any cause other than HIV infection. The HIV–associated aneurysmal arteriopathy is a rare cerebrovascular complication of acquired immune deficiency syndrome (AIDS) and has been the subject of several case reports and case series involving children, and more recently adults, with AIDS.…”
mentioning
confidence: 99%
“…Despite the void of evidence from controlled trials in this area, the reports that exist suggest a trend towards treating these patients with thrombolysis or endovascular clot extraction to improve their clinical and functional outcome. However, it is clear that patients who commence treatment with antithrombotic agents of any type while they have only moderately disabling signs have a better outcome than those that are only treated when they are already locked-in [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include clot aspiration, angioplasty and stenting, laser treatment, ultrasound, and clot retrieval [ 20 , 21 , 25 -28 ]. The Basilar Artery International Cooperation Study (BASICS) was a prospective observational study of 592 patients with radiologically confi rmed basilar artery occlusion [ 19 ]. In this study the patients were divided into three groups according to the treatment they received; antithrombotic therapy alone (AT), primary intravenous thrombolysis (IVT) including subsequent IA thrombolysis, or intra-arterial therapy (IAT) which included thrombolysis, mechanical clot retrieval, stenting or a combination of these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Kure et al demonstrated the presence of HIV within the arterial wall of the circle of Willis and in the cerebral parenchy ma in a child who died of HIVrelated cerebral vascular ectasia and multiple infarcts [63]. Schieffelin et al, with 51 subjects with diagnoses suggestive of CNS vasculop athy among the 3338 HIV+ subjects and after review, excluded 27 as not being consistent with CNS vasculop athy [64]. They indicated that despite being a rare event, the incidence rate of stroke is higher than the reported incidence rate of stroke in the general paediatric pop ulation, so they concluded that there is increased in cidence of cerebrovascular events in HIV+ children, with the incidence among the HIV+ subjects being 2.4 times that of HEU subjects [64].…”
Section: Hiv and Stroke In Childrenmentioning
confidence: 99%